The effect of microbial polysaccharides on the properties of wheat flour - Самохвалова, Ольга Володимирівна; Чернікова, Юлія Олександрівна; Олійник, Світлана Георгіївна; Касабова, Катерина Рубенівна (Eastern-European Journal of Enterprise Technologies, 2015)
The paper presents a comparative analysis of the influence of microbial polysaccharides ksampan and enposan on the technological properties of wheat flour. It is proved that the presence of either ksampan or enposan strengthens the gluten, increases its firmness, and reduces its extensibility. Alveograms show an increase in the dough firmness, whereas farinograms demonstrate that the dough water absorption capacity and stability grow while its liquefaction and elasticity decrease. This can be explained both by the strengthened fibrinous frame of the flour and a “reinforcing” effect of the hydrated polysaccharide molecules. It is proved that microbial polysaccharides accelerate the process of starch pasting, increase the viscosity of the flour slurry, and increase the stability of starch paste during thermal and mechanical operations. Summarizing the findings, we can say that the effect of enposan on the biopolymers of wheat flour is similar to that of ksampan, but slightly smaller. Thus, enposan can be recommended for stabilizing of flour dough systems.